Evaluating compliance with local and International Food Labelling Standards in urban Tanzania: a cross-sectional study of pre-packaged snacks in Dar Es Salaam - Hassan Rusobya; Fredirick Mashili; Ashabilan A Ebrahim; Zuhura Kimera (BMC, 2024)
Abstract Background Urbanization influences food culture, particularly in low- and middle-income countries where there is an increasing consumption of processed and pre-packaged foods. This shift is contributing to a rise in non-communicable diseases. Food labelling standards are crucial for regulating manufacturing practices and helping consumers make healthy food choices. We aimed to assess the compliance of local and imported pre-packaged snacks with Tanzanian and international labelling standards in Dar es Salaam, Tanzania. Methodology A cross-sectional study was conducted on 180 snack products. A checklist based on Tanzanian and Codex labelling standards was used to evaluate adherence. We also examined factors influencing adherence, such as product origin, price, category, purchase location, and package size. Results The majority of the snacks demonstrated partial adherence to Tanzania (n = 97; 54%) and International (Codex) (n = 120; 67%) labelling standards. Imported products showed significantly better adherence to both Tanzanian (n = 46; 53%) and international (n = 42; 48%) standards. Notably, more than half (n = 110; 66.7%) of the products used English for labelling, and infrequently (n = 74; 41.4%) used the recommended World Health Organization Front-of-Pack Nutrition Labelling. Product category, origin, and package size were significantly associated with higher levels of international standard adherence (p < 0.05). Conclusion The inadequate adherence to mandatory labelling standards and the scarce use of Swahili and FoPL highlight the need to strengthen labelling practices and potential challenges faced by consumers in understanding nutritional information. Thus, strengthening and emphasizing good labelling practices are urgently needed as we seek to address diet-related noncommunicable diseases.